Adverse Events as a Potential Clinical Marker of Antitumor Efficacy in Ovarian Cancer Patients Treated With Poly ADP-Ribose Polymerase Inhibitor - Ni, Jing; Cheng, Xianzhong; Zhou, Rui; Zhao, Qian; Xu, Xia; Guo, Wenwen; Gu, Hongyuan; Chen, Chen; Chen, Xiaoxiang (Frontiers in Oncology, 2021)
Background PARP inhibitor (PARPi) is an important progress in ovarian cancer treatment. The available evidence suggests that BRCA mutation and homologous recombination deficiency (HRD) are effective biological markers for PARPi. Here we investigated the relationship between adverse events (AEs) and efficacy of PARPi in ovarian cancer patients. Methods Seventy-eight patients with ovarian cancer patients underwent Olaparib and Niraparib from July 2018 to July 2020 were analyzed. AEs were assessed by the National Cancer Institute Common Terminology Criteria for Adverse Events (NCI CTCAE) v5.0. Chi-square test or fisher exact tests was performed to observe the association between categorical variables. Logistic regression analysis was conducted to investigate the independent variables for disease control response (DCR). Progression-free survival (PFS) was compared between AEs variables by log-rank test. Results Patients with AEs in the first one week had a higher DCR compared with those after one week (86.11% versus 60.98%, p=0.013). Patients with serious AEs (SAEs) had a significantly higher DCR (81.40% versus 60.60%, p=0.045). There were associations between anemia and DCR in both occurrence (79.63% versus 56.52%, p=0.037) and grade (100% versus 73.17%, p=0.048). The median PFS of patients with hematological toxicity was longer than that of patients with no-hematological toxicity (30 versus 20 weeks, p=0.047). Patients with hematological toxicity within four weeks had prolonged median PFS than those with hematological toxicity after four weeks (40 versus 22 weeks, p=0.003). Conclusions The early presence of AEs and SAEs in hematological toxicity of PARPi were related to the antitumor efficacy, which might be a valid and easily measurable clinical marker in ovarian cancer patients.